2016
DOI: 10.1002/etc.3324
|View full text |Cite
|
Sign up to set email alerts
|

Net methylmercury production in 2 contrasting stream sediments and associated accumulation and toxicity to periphyton

Abstract: Periphyton uptake of bioaccumulative methylmercury (MeHg) may be an important entryway into the food web of many stream ecosystems where periphyton can be dominant primary producers. The net production of MeHg in stream sediment, its bioaccumulation in periphyton, and the potential toxicity of divalent Hg (Hg[II]) and MeHg in sediment to periphyton were investigated with a 67-d in situ incubation experiment using chemical exposure substrates containing either a fine-grained, organic-rich or a sandy, low-organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The transient, often reversible, effects of contaminants, including metals such as Ag, Cd, Cu, Pb, and Zn on photosynthesis, pigment composition, enzymatic activities, nucleic acid incorporation are most often used to characterize metabolic and physiological perturbations over short‐term exposure and to determine biomarkers for early effects . Nonetheless, no effect on metabolism has been observed in biofilms exposed to sediments enriched with Hg concentrations up to 59 μg g −1 dry weight sediment . Based on experiments with isolated microorganisms, it can be anticipated that exposure to high Hg concentrations will negatively affect photosynthesis, increase reactive oxygen species, induce phytochelatin synthesis, and affect nutrient metabolism .…”
Section: Hg Toxicity To Freshwater Biofilmsmentioning
confidence: 99%
“…The transient, often reversible, effects of contaminants, including metals such as Ag, Cd, Cu, Pb, and Zn on photosynthesis, pigment composition, enzymatic activities, nucleic acid incorporation are most often used to characterize metabolic and physiological perturbations over short‐term exposure and to determine biomarkers for early effects . Nonetheless, no effect on metabolism has been observed in biofilms exposed to sediments enriched with Hg concentrations up to 59 μg g −1 dry weight sediment . Based on experiments with isolated microorganisms, it can be anticipated that exposure to high Hg concentrations will negatively affect photosynthesis, increase reactive oxygen species, induce phytochelatin synthesis, and affect nutrient metabolism .…”
Section: Hg Toxicity To Freshwater Biofilmsmentioning
confidence: 99%
“…Anoxic sediments have long been considered the primary location of MMHg production ( 4 ), but their central role in MMHg production has been recently challenged by studies on Hg transformations in littoral biofilms (i.e., periphyton) ( 5 , 6 ), which consist of heterogeneous communities of photosynthetic and heterotrophic microorganisms attached to a submerged substrate ( 7 ). Periphyton was previously shown to be an important site of Hg accumulation ( 8 10 ) and a source of Hg for entry into benthic trophic webs ( 11 , 12 ). However, knowledge gaps remain on the contribution of periphyton to Hg cycling in boreal aquatic environments, specifically on the capacity of periphyton to produce MMHg.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, periphyton has been identified as the principal entry point for methylmercury in an Amazonian region (Roulet et al, 2000). Indeed, several studies have shown that periphyton supports high Hg methylation rates due to microbial activity in tropical ecosystems (Guimarães et al, 1998;Acha et al, 2005, Klaus et al 2016.…”
Section: Samplingmentioning
confidence: 99%